The Effect of septoplasty on physical performance - Śliwiak, Patryk; Kondratowicz, Aneta; Miłkowski , Paweł; Głąbień, Marta; Aleksandrowicz, Daria; Kuśnierz, Anna; Jakubczak, Zofia; Kusiak, Karolina; Wieczorek, Olga; Zimniak, Maria Weronika (Quality in Sport, 2024)
The nasal septum is a key component of the nasal structure, affecting proper airflow and providing support for the nasal structures. A deviated septum (DSN) can lead to breathing disorders, impaired nasal patency, recurrent nosebleeds, olfactory disorders and frequent upper respiratory tract infections. In competitive sports, where ventilation performance is critical, septal deviation can adversely affect athletic performance. The purpose of this study is to evaluate the effect of septoplasty on patients’ physical performance. Methodes This article is based on the available literature found in the Google Scholar, PubMed database with the use of key words such as , septoplasty’’, , nasal septal deviation’’, , septoplasty quality of life’’, , nasal septal deviation athletes’’, , septoplasty sport’’, , nasal obstruction sport’’. Results Conducted studies show that surgical correction of a deviated nasal septum improves physical performance as well as respiratory and cardiovascular functions. Restoring proper airflow through the nose after surgery leads to a noticeable improvement in physical performance, highlighting the significance of septoplasty in enhancing patient comfort and improving athletic outcomes.